A Citizen’s Democracy in Authoritarian Times: An American View on the Catalan Drive for Independence (2018)
Agents of sedition who are heedlessly destroying Spain’s “consolidated democracy”? Xenophobes simply interested in protecting their own wealth who are, behind the rhetoric, not that different from the tribal authoritarians coming to the fore in Hungary and northern Italy? These are but two of the many narrative tropes the Spanish government and the establishment press in Europe and the US are rolling out to counter the rise of separatist sentiment in Catalonia. In this book, Thomas S. Harrington, an American with a deep familiarity with Catalan culture and history, argues that, far from being a threat to democracy in Europe, the scrupulously peaceful and people-driven movement for independence in Catalonia is, perhaps, the best hope we have for spurring its much hoped-for renewal.¿Agentes de sedición que están destruyendo despreocupadamente la "democracia consolidada" de España? ¿Xenófobos simplemente interesados en proteger su propia riqueza que, detrás de la retórica, no son tan diferentes de los autoritarios tribales que surgen en Hungría y el norte de Italia? Estos son sólo dos de los muchos tropos narrativos que el gobierno español y la prensa del “establishment” en Europa y los EE.UU. están desplegando para contrarrestar el auge del sentimiento separatista en Cataluña. En este libro, Thomas S. Harrington, un estadounidense con un profundo conocimiento de la cultura y la historia catalanas, argumenta que, lejos de ser una amenaza para la democracia en Europa, el movimiento independentista, escrupulosamente pacífico e impulsado por el pueblo, en Cataluña es, quizás, la mejor esperanza que tenemos para impulsar su tan esperada renovación.
Keywords: Politics; Culture; media; perception managment; Catalonia; Spain; Nationalism; Iberian culture; European politics; Independence movements; EU; repression; Democracy; authoritarianism; Spanish Transition; Catalan History; Historycitizenship